Project-based learning in teaching English for ESL students: A path to engagement and mastery - Yusupova , Nilufar (The Lingua Spectrum, 2025)
Project-based learning (PBL) is an innovative and student-centered teaching approach that has proven effective in engaging English as a Second Language (ESL) students. By integrating real-world tasks and collaborative problem-solving into the language learning process, PBL provides students with meaningful opportunities to practice and master English in authentic contexts. This approach not only enhances linguistic skills but also fosters critical thinking, creativity, and teamwork. Through carefully designed projects that align with curriculum goals and cater to students' interests, educators create a dynamic learning environment where learners actively participate and apply language skills to practical challenges. PBL encourages intrinsic motivation, as students see the relevance of their learning to real-life scenarios, and it promotes deeper understanding by connecting language acquisition with hands-on experiences. This article examines the principles of PBL, its application in ESL education, and strategies to optimize its effectiveness in fostering language proficiency and learner engagement.